Recent Developments and Trends in Accounting Information Systems - Georgantopoulos, Andreas G.; Poutos, Evangelos I.; Eriotis, Nikolaos (Journal of Accounting, Business and Finance Research, 2018)
This study examines the relationship between management accounting and integrated information systems by investigating the existing literature on the subject. The current research has been uncovered, classified and interpreted in order to provide an understandable illustration of the findings of previous studies and to show in what aspects more research is required. This paper also provides a new theoretical framework which enables a structured classification of the reviewed literature.